Analisis Rasio Keuangan Pt Semen Indonesia Tbk. Periode 2018-2022 - Yunita, Anggraeni; Andini, Tiara; Yunita, Nurma; Saiwa Azmy, Muhammad Adji; Pitriana; Anggela, Pipin (Indonesian Journal of Accounting and Business, 2024)
Manufacturing companies are one of the choices that many investors are interested in investing in, one of which is PT Semen Indonesia Tbk. which is the largest cement producer in Indonesia. The aim of this research is to examine and analyze the financial performance of PT Semen Indonesia Tbk. period 2018 – 2022 with tools to measure liquidity, solvency, profitability and activity ratios. The method used in this research is descriptive qualitative, with quantitative data sourced from secondary data, with data collection techniques in the form of documentation. The results of this research are based on Liquidity Ratios, Solvency Ratios show less good results compared to the current industry average. However, if we look at the Gross Profit Margin, it shows good results compared to the current industry average, and the Activity Ratio shows less than optimal results compared to the current industry average. Keywords: Liquidity, Solvency, Profitability, Activities